2016
DOI: 10.1123/jcsp.2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Evaluation of a Method to Assist Recruitment of Participants Into Treatment Outcome Research and Engage Student-Athletes Into Substance Abuse Intervention

Abstract: Recruitment of participants into treatment outcome studies is an important and often challenging aspect of human research. Yet, there have been very few controlled trials that have examined methods of recruiting participants into clinical trials, particularly in populations that may be reluctant to pursue mental health intervention, such as athletes. In this study, 79 NCAA Division I, Club, and Intramural student-athletes volunteered to participate in a study to determine their interest in participating in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…We identified seven intervention studies designed to decrease barriers to athlete mental health treatment-seeking. Despite improving mental health knowledge and decreasing stigma attached to mental health disorders, these studies reported no effects on mental health treatment-seeking 40 41 49 50 58–60. Generally, the interventions were short-term, aiming to increase awareness and understanding of mental health, decrease stigma attached to it, and reduce overall barriers to accessing mental health supports and services for athletes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified seven intervention studies designed to decrease barriers to athlete mental health treatment-seeking. Despite improving mental health knowledge and decreasing stigma attached to mental health disorders, these studies reported no effects on mental health treatment-seeking 40 41 49 50 58–60. Generally, the interventions were short-term, aiming to increase awareness and understanding of mental health, decrease stigma attached to it, and reduce overall barriers to accessing mental health supports and services for athletes.…”
Section: Resultsmentioning
confidence: 99%
“…Donohue et al 59 tested two semi-structured interview formats: one interview focused on discussing the athlete’s experiences in sports, and the other focused on describing sport psychology and its potential benefits to the athlete. Donohue et al 60 conducted a subsequent study to determine interest in participating in one of two goal-oriented programmes. Donohue et al 58 also tested a sport-specific optimisation approach to concurrent mental health and sport performance, which consisted of a longer intervention, with 12 performance meetings of 60 to 90 min within 4 months.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies may lead athletes to realize that mental health programs are capable of assisting them in athletic performance optimization. The use of engagement strategies is another tool that may increase referrals to psychologically based optimization programs (Donohue et al, 2016). Indeed, it will be important for professional organizations to proactively adopt such practices while mandating athletes to participate in psychometrically validated mental health screening procedures that are aimed at identifying athletes who either evidence mental health conditions, or are at risk to develop them.…”
Section: Access and Barriers To Carementioning
confidence: 99%
“…No significant between‐group intervention effects were found in service utilization, although the intensive intervention reduced stigma associated with mental health relative to the control condition. Donohue et al (2016) compared standard engagement (SE) with SE plus discussion of mental health/substance use in collegiate athletes. Results demonstrated that participants who were randomly assigned to the more involved engagement condition were more likely to consent to participate in goal‐oriented intervention specific to sport and life in general, but no significant intervention effects were found in therapeutic attendance.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have cautioned about using self‐reports of willingness and intentions as proxies for actual behavioral treatment attendance (see comprehensive review by Moreland et al, 2018). To our knowledge, only three studies involving collegiate athletes have examined psychological help seeking behavior (i.e., attendance) as an identified outcome in controlled research (Donohue et al, 2004; Donohue et al, 2016; Gulliver et al, 2012a). Therefore, determining factors that are likely to influence actual mental health service utilization may assist outreach efforts and intervention development.…”
Section: Introductionmentioning
confidence: 99%